Comparison of processing speed, balance, mobility and fear of falling between hypertensive and normotensive individuals - Ozaldemir, Isilay; Iyigun, Gozde; Malkoc, Mehtap (Associacao Brasileira Pesquisa Pos-Graduacao Fisioterapia-Abrapg-Ft, 2020)
Background: Hypertension (HT) contributes substantially to poor physical function, cognitive dysfunction, cardiovascular problems and to all-cause mortality. Performance in activities requiring attention, speed and coordination might also be affected in individuals with HT. Objective: This study compared the processing speed, static and dynamic balance, functional mobility and fear of falling between individuals with hypertension (HT group) and normotensive individuals (NT group). Methods: One-hundred and twenty-eight individuals were included: NT group (n = 64) and HT group (n = 64). The Choice Stepping Reaction Time Test was used for the evaluation of processing speed, Single Leg Stance test for static balance evaluation, Y Balance Test for dynamic balance evaluation, Timed Up and Go test with single and dual tasking for the evaluation of functional mobility and Falls Efficacy Scale for assessing fear of fatting. Results: The processing speed of the HT group was slower than that of the NT group; the total response time (RsT) in Stepping Reaction Test (SRT) (mean difference [MD] = -0.2, 95% CI= -0.3, 0), and Stroop Test (ST) [ST-A (MD = -0.4, 95% CI = -0.5, -0.2), ST-B (MD = -0.5, 95% CI = -0.7, -0.2) and ST-C (MD = -0.6, 95% CI = -0.8, -0.3). Additionally, the static [single leg stance, eyes open, right side (MD = 12.7, 95% CI = 6.3, 19.0) and left side (MD =13.6, 95% CI = 7.2, 19.9)] and dynamic balance [Y balance test, composite score, right tower extremity (MD = 8.5, 95% CI = 4.4, 12.5) and left lower extremity (MD = 5.2, 95% CI = 1.5, 8.8) scores of the HT group were tower than those of the NT group. The HT group required a longer time to complete the functional mobility test measured with Timed Up And Go Test during both single task (MD = -0.8, 95% CI = -1.1, -0.4), cognitive dual task (MD = -1.5, 95% CI = -2.4, -0.5) and manual dual task (MD = -0.9, 95% CI = -1.3, -0.4) in comparison to the NT group. Also, the HT group had higher levels of fear of falling (MD = -7.6, 95% CI = -10.9, -4.2). Conclusion: Hypertensive individuals present slower processing speed, reduced static and dynamic balance, decreased functional mobility and higher fear of falling in comparison to normotensive individuals. (C) 2019 Associacao Brasileira de Pesquisa e Pos-Graduacao em Fisioterapia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Blood pressure; Reaction time; Dual task; Falling; Rehabilitation